2022
DOI: 10.1021/acs.jafc.2c05697
|View full text |Cite
|
Sign up to set email alerts
|

CircSETBP1 Acts as a MiR-149-5p Sponge to Promote Intramuscular Fat Deposition by Regulating CRTCs

Abstract: Circular RNAs (circRNAs) appear to be crucial in the process of adipogenesis according to mounting data. CircSETBP1 is a newly discovered circRNA associated with adipogenesis. Sequencing verification and RNase R treatment have confirmed the circular nature of circSETBP1 in porcine tissue. The precise function and mechanism of circSETBP1 in adipocyte biology are still unclear. Cell counting kit-8 (CCK8), Oil red O staining, and quantitative real-time polymerase chain reaction (qRT-PCR) were employed in this inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“… 12 In a separate study, it was revealed that CircSETBP1 expedites the differentiation of intramuscular preadipocytes and 3T3-L1 cells by modulating the miR-149-5p/CRTCs axis, consequently curtailing cell proliferation. 30 Through gain or loss-of-function experiments, we have confirmed that circMEF2C(2, 3) exerts a dual regulatory role in porcine intramuscular preadipocytes. Specifically, we observed that circMEF2C(2, 3) enhances cell proliferation while concurrently inhibiting the differentiation of these cells into mature adipocytes.…”
Section: Discussionmentioning
confidence: 58%
“… 12 In a separate study, it was revealed that CircSETBP1 expedites the differentiation of intramuscular preadipocytes and 3T3-L1 cells by modulating the miR-149-5p/CRTCs axis, consequently curtailing cell proliferation. 30 Through gain or loss-of-function experiments, we have confirmed that circMEF2C(2, 3) exerts a dual regulatory role in porcine intramuscular preadipocytes. Specifically, we observed that circMEF2C(2, 3) enhances cell proliferation while concurrently inhibiting the differentiation of these cells into mature adipocytes.…”
Section: Discussionmentioning
confidence: 58%
“…Porcine IM preadipocytes were isolated from 3-day-old Queshan Black piglets by using the published method [ 42 ]. The improved Eagle medium contains 89% Durbeko (Gibco, Carlsbad, USA), 10% FBS (Gibco, Carlsbad, USA), and 1% penicillin-streptomycin (Solarbio, Beijing, China) growth medium to cultivate porcine IM preadipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-149 controls non-alcoholic fatty liver disease by targeting FGF-21 [ 40 ]; it also inhibits the ATF6 pathway to reduce inflammation and apoptosis in nonalcoholic fatty liver disease brought on by endoplasmic reticulum stress [ 41 ]. According to Liu et al, miR-149-5p reduces the differentiation of porcine IM preadipocytes and 3T3-L1 cells while promoting their growth [ 42 ]. However, it is still unclear how miR-149-5p influences the development of porcine IM preadipocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine IM preadipocytes were isolated from 3-day-old Queshan black piglets using the published method [43]. The improved Eagle medium contains 89% Durbeko (Gibco, Carlsbad, USA), 10% FBS (Gibco, Carlsbad, USA), and 1% penicillin-streptomycin (Sulaibao, Beijing, China) growth medium to cultivate porcine IM preadipocytes.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…MiR-149 controls non-alcoholic fatty liver disease by targeting FGF-21 [41]; it also inhibits the ATF6 pathway to reduce in ammation and apoptosis in nonalcoholic fatty liver disease brought on by endoplasmic reticulum stress [42]. According to Liu et al, miR-149-5p reduced the differentiation of porcine IM preadipocytes and 3T3-L1 cells while promoting their growth [43]. However, the exact way by which miR-149-5p affects porcine IM preadipocyte development is unknown.…”
Section: Introductionmentioning
confidence: 99%